Normal pressure hydrocephalus: an update - Passos-Neto, Carlos Eduardo Borges; Lopes, Cesar Castello Branco; Teixeira, Mauricio Silva; Studart, Adalberto, Neto; Spera, Raphael Ribeiro (Arquivos de Neuro-Psiquiatria, 2022)
Normal pressure hydrocephalus (NPH) has been a topic of debate since its introduction in publications. More frequent in the elderly population, it is characterized by gait disturbance, urinary urge incontinence and cognitive decline. Therefore, it is a clinical-radiological entity with relatively common findings for the age group, which together may have greater specificity. Therefore, its diagnosis must be careful for an adequate selection of patients for treatment with ventricular shunt, since the symptoms are potentially reversible. The tap test has a high positive predictive value as a predictor of therapeutic response, but a negative test does not exclude the possibility of treatment. Scientific efforts in recent years have been directed towards a better understanding of NPH and this narrative review aims to compile recent data from the literature in a didactic way for clinical practice.
Keywords: Hydrocephalus, Normal Pressure; Dementia; Spinal Puncture